A Study on the Licensing Process for the Floating Nuclear Power Plant in Indonesia: A Suggestion for the Revision of Government Regulation Regarding Nuclear Power Plant Licensing - Fery Putrawan Cusmanri; Hak-kyu Lim (Energies)
Indonesia is currently revising some Government Regulations regarding the licensing process of the nuclear power plant. In the current revision process, the latest technology such as small modular reactors and floating nuclear power plants are also considered to be regulated specifically. In current regulations, regardless of the type and technology, the licensing for nuclear power plants is regulated generally. Considering its unique nature and character, the floating nuclear power plant should have more specific requirements for the licensing process. This paper is carried out to analyze the specific requirements that should be considered for the licensing process of the floating nuclear power plant in Indonesia. The results of this study are expected to be a suggestion for the Government Regulations revision.